Agent-based group decision support in medicine - Duarte, Júlio (2009)
Cancer staging is the process by which physicians evaluate the spread of cancer. This is important, once in a good cancer staging system, the stage of disease helps to determine prognosis and assists in selecting therapies. A combination of physical examination, blood tests, and medical imaging is used to determine the clinical stage; if tissue is obtained via biopsy or surgery, examination of the tissue under a microscope can provide pathologic staging. On the other hand, good patient education may help to reduce health service costs and improve the quality of life of people with chronic or terminal conditions. In this paper it is endorsed a theoretical based model to support the provision of computer based information on cancer patients, and the computational techniques used to implement it. One’s goal is to develop an interactive agent based computational system which may provide physicians with the right information, on time, that is adapted to the situation and process-based aspects of the patients’s illness and treatment.